Biological and synthetic mesh assisted breast reconstruction procedures: Joint guidelines from the Association of Breast Surgery and the British Association of Plastic, Reconstructive and Aesthetic Surgeons. Issue 11 (November 2021) - Whisker, Lisa; Barber, Matthew; Egbeare, Donna; Gandhi, Ashu; Gilmour, Adam; Harvey, James; Martin, Lee; Tillett, Rachel; Potter, Shelley
Abstract: These guidelines have been produced with the involvement of the Association of Breast Surgery and the British Association of Plastic, Reconstructive and Aesthetic Surgeons. Recommendations have been derived after a review of published data regarding the use of acellular dermal matrix (ADM), biological and synthetic mesh in breast reconstruction. The guidelines represent a consensus opinion on the optimal management of patients having biological or synthetic mesh assisted breast reconstruction informed by peer-review publications. The Guidelines should be used to inform clinical decision making. Ultimately, members of the MDT remain responsible for the treatment of patients under their care.